A fiberglass and resin post technique combined with fragment collage of an upper central incisor : multidisciplinary treatment = Unión de fragmento de un incisivo central superior con una técnica combinada : tratamiento multidisciplinario - Ramírez Barrantes, Juan Carlos 1964-
The clinical treatment of anterior tooth fractures requires specialized knowledge, technical skill, and a degree of artistic sense to ensure successful treatment. Herein, we describe the reattachment of an original tooth fragment with endodontic involvement via the utilization of a micro-hybrid composite resin and an aesthetic fiberglass post.